Maritime clusters and their development interplay with ports - Zhang Wei (2015)
Recent research shows that maritime clusters can maximise competitive advantages in maritime and regional development. Thus the promotion of maritime clusters has been taken as an important policy tool when considering an array of linked sectors in the maritime industry from the network perspective. Of all the sectors in a maritime cluster, the port plays an important role in cluster development. This research aims to study the maritime cluster concept and evolution and its interrelationship with port development, which are identified as the gaps in the study of maritime clusters. The analysis starts with an overview of maritime cluster, which is not a static concept, but an evolutionary one based on the dynamics of its functions. The role of the port in a maritime cluster changes according to the different maritime cluster categories, which can be divided into four types. These are centre of cargo loading and discharging; centre of cargo distribution and value-added process; node of regional/global supply chain, and international maritime service centre. Based on the innovative conceptual development of the classification and evolution of maritime clusters from a changing port functions perspective, this research takes further steps to identify ten major world maritime clusters and sixteen maritime sectors that contribute to maritime cluster development. This is conducted by descriptive statistics analysis, questionnaire survey and interview methods. Two case examples, namely London and Hong Kong, are drawn from these clusters, showing a port’s contribution to maritime cluster development. In addition, special attention is paid to drawing implications for Singapore. To anticipate the path of further development for maritime clusters, the relationship between a port and other maritime sectors is studied. To solve this problem from a maritime cluster evolution perspective, a multi-mode framework is proposed by adopting an interdisciplinary study. With thorough analogical analysis between maritime cluster and biotic community in a biological system, the Lotka-Volterra model in biological science is introduced for application in maritime cluster studies. In order to identify the development path and priority for maritime clusters, port efficiency is measured by the modified Super-Efficiency Data Envelopment Analysis (SE-DEA) method. It aims to evaluate the validity of support and utilisation between the port and maritime clusters. This research presents a useful reference for research and policy suggestions on the interplay and evolution between a maritime cluster and its port development for maritime cities and regions en route to becoming higher-value-generating international maritime centres.